The Analysis of System Constraints in National Treasure 2: Book of Secrets Movie - Syam, Andi Tenrisanna (Language Circle: Journal of Language and Literature, 2019)
This paper discussed about system constraints in ‚National Treasure 2: Book of Secrets‛ movie. The writer used the qualitative research with discourse analysis approach to explain the content of this paper. There were two data sources; it was the primary data and secondary data. The primary data were movie and the movie script of ‚National Treasure 2: Book of Secrets‛. The secondary data source were got from books, essays, articles, magazines, internet and journals. In this research, the writer used documentation as the way to collect the data. Documentation was movie script. The writer found that: (1) some people would open communication with various ways by saying: hi, hello, good afternoon, and introduce himself, (2) during 45 minutes those were 4 conversations on mobile phone. Two of them do not use an open signal, (3) there are verbal communication such as; OK, yeah, uh-huh, well, all right, and uh and non-verbal communication such as: smiling, head nodding, laughing, eye contacting, and increasing volume of voice, (4) these are a lot of statements that can be interpretable and hearable, (5) bracket signals in this movie such as intonation and shifts in body position, (6) overlaps (not-interruptions) do happen in this movie, (7) nonparticipant move to be participant by repeat sentence that he overhears in the ongoing conversation and non-verbal signal (gazing steadily), (8) the bracket signals are intonation and shifts in body position, (9) the preempt signals found in the movie are: no...no, excuse me, hoi, with respect and I am sorry, and (10) the Grice maxim of relevant is ignored.